SEWAGE SLUDGE COMPOST ASSOCIATED TO FREQUENCY OF IRRIGATION FOR Peltophorum dubium (Sprengel) Taubert SEEDLINGS PRODUCTION - Oliveira Cleto da Silva, Laura; da Fonseca, Aline Cássia; Lozano Sivisaca, Deicy Carolina; Ribeiro da Silva, Magali; Lyra Villas Boas, Roberto; Amaral Guerrini, Iraê (Floresta, 2020)
Inappropriate disposal of sewage sludge has become an environmental problem. In some Brazilian states, such as São Paulo, in natura sewage sludge use is practically prohibited due to restrictive requirements by CONAMA Resolution No. 375/2006. Therefore, a very promising alternative to reuse this residue is to compost it with other materials and use it as a substrate in the production of seedlings. The objective of this study was to evaluate the development of the seedlings of Peltophorum dubium in compost with sewage sludge, to determine which frequency of irrigation would be more adequate according to the physical characteristics of each substrate, and if this would influence the morphological and nutritional variables of the seedlings. Two composts were produced: sewage sludge composted with sugarcane bagasse and sewage sludge composted with eucalyptus bark, both in 1: 1 proportion. Commercial substrate was used for control. This study was completely randomized in a 3x3 factorial design, which three substrates and three frequencies of irrigation were tested: two, three and four times per day. The evaluated parameters were: plant height, stem diameter ratio, shoot / root ratio, leaf dry mass, root dry mass, total dry mass, green color index, Dickson quality index (IQD), water loss through leaching and substrate water retain capacity. The best results were observed in the seedlings produced in sewage sludge compound with eucalyptus bark submitted to the frequencies of two or three times a day.